Asiaticoside induces cell proliferation and collagen synthesis in human dermal fibroblasts - Linda Yuliati; Etik Mardliyati; Kusmarinah Bramono; Hans Joachim Freisleben (Faculty of Medicine, Universitas Trisakti, 2015)
BackgroundAsiatiocoside, a saponin component isolated from Centella asiatica can improve wound healing by promoting the proliferation of human dermal fibroblasts (HDF) and synthesis of collagen. The skin-renewing cells and type I and III collagen synthesis decrease with aging, resulting in the reduction of skin elasticity and delayed wound healing. Usage of natural active compounds from plants in wound healing should be evaluated and compared to retinoic acid as an active agent that regulates wound healing. The aim of this study was to compare and evaluate the effect of asiaticoside and retinoic acid to induce greater cell proliferation and type I and III collagen synthesis in human dermal fibroblast.MethodsLaboratory experiments were conducted using human dermal fibroblasts (HDF) isolated from human foreskin explants. Seven passages of HDF were treated with asiaticoside and retinoic acid at several doses and incubated for 24 and 48 hours. Cell viability in all groups was tested with the MTT assay to assess HDF proliferation. Type I and III collagen synthesis was examined using the respective ELISA kits. Analysis of variance was performed to compare the treatment groups. ResultsAsiaticoside had significantly stronger effects on HDF proliferation than retinoic acid (p<0.05). The type III collagen production was significantly greater induction with asiaticoside compared to retinoic acid (p<0.05). ConclusionAsiaticoside induces HDF proliferation and type I and III collagen synthesis in a time- and dose-dependent pattern. Asiaticoside has a similar effect as retinoic acid on type I and type III collagen synthesis.